PENAFIAN AKSES: RUJUKAN KEPADA KES-KES YANG DIPUTUSKAN DI MAHKAMAH SYARIAH DI MALAYSIA: Access Denial: Reference to the Cases Decided in the Shariah Court in Malaysia - Noor, Zanariah (Jurnal Syariah, 2014)
This article discusses rights of access and the issue of denying access to a parent or party with an access order as well as a parent’s refusal to hand over the children to the party with a custody order. In some cases, it has even led to the abduction of children by the party whose access was denied. Denying a parent the right of access to his/her children is not only an act of breaching the law but also an act of committing sin to the denied parent as well as to the children. In fact, for their emotional and physical well-being, children are entitled to continue their relationship with both parents.